Rancang Bangun Sistem Presensi Berbasis Internet of Things Pada PT. Roda Maju Bahagia - Silvia Carmelita Febrianti; Edy Siswanto; Bagus Sudirman (Elkom: Jurnal Elektronika dan Komputer, 2026)
This research is intended to develop an Internet of Things (IoT)-based attendance system that enhances the efficiency of attendance data management at PT. Roda Maju Bahagia, where the previous process was still carried out manually. Human error during manual attendance management became one of the main issues, accompanied by inefficient data recording, obstacles in data retrieval and archiving, and limited accuracy in reporting. This research applied a qualitative method using a Research and Development (R&D) approach based on a prototype model. The attendance device/machine was built using a microcontroller circuit. Fingerprint reading results were then sent to a database, and notifications were sent to employees' Telegram accounts. All of this was done via a Wi-Fi or internet connection. The system featured automatic daily and monthly attendance reporting on a local website managed by HR administrators, utilizing attendance data obtained from the fingerprint device. Reports can be downloaded in Excel or PDF format, in tabular format, according to management and company needs. The results indicated that the system was able to record, process, and display attendance reports effectively. This system implementation has improved the efficiency, accuracy, and transparency of attendance records used for payroll calculations, thereby enhancing human resource management performance.